2016
DOI: 10.1002/chem.201604583
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Oligothiophenes Compete for Binding of X‐34 but not PIB to Recombinant Aβ Amyloid Fibrils and Alzheimer's Disease Brain‐Derived Aβ

Abstract: Deposits comprised of amyloid‐β (Aβ) are one of the pathological hallmarks of Alzheimer's disease (AD) and small hydrophobic ligands targeting these aggregated species are used clinically for the diagnosis of AD. Herein, we observed that anionic oligothiophenes efficiently displaced X‐34, a Congo Red analogue, but not Pittsburgh compound B (PIB) from recombinant Aβ amyloid fibrils and Alzheimer's disease brain‐derived Aβ. Overall, we foresee that the oligothiophene scaffold offers the possibility to develop no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 25 publications
2
45
0
Order By: Relevance
“…In contrast, the negatively charged tTBT2, displayed staining of both Aβ and tau aggregates (Figure , Supporting Information Figures S1 and S2). Thus, similar to what has been reported earlier for oligothiophenes, anionic carboxyl groups along the tTBT backbone might be an essential chemical determinant for achieving high‐affinity optical ligands towards protein aggregates. However, none of the tTBTs displayed selective staining towards tau pathology, signifying that the bTVBT molecular scaffold was superior for achieving optical ligands that selectively detect tau deposits in brain sections with AD pathology.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…In contrast, the negatively charged tTBT2, displayed staining of both Aβ and tau aggregates (Figure , Supporting Information Figures S1 and S2). Thus, similar to what has been reported earlier for oligothiophenes, anionic carboxyl groups along the tTBT backbone might be an essential chemical determinant for achieving high‐affinity optical ligands towards protein aggregates. However, none of the tTBTs displayed selective staining towards tau pathology, signifying that the bTVBT molecular scaffold was superior for achieving optical ligands that selectively detect tau deposits in brain sections with AD pathology.…”
Section: Resultssupporting
confidence: 77%
“…Hence, q‐FTAA‐CN and bTVBT3 most likely have alternative modes of binding to tau aggregates. Previous studies have suggested that anionic oligothiophenes, including q‐FTAA‐CN, have a similar mode of binding to protein aggregates as Congo red and related analogues ,. Anionic oligothiophenes efficiently displaced X‐34, a Congo Red analogue, but not Pittsburgh compound B (PIB) from recombinant Aβ amyloid fibrils and Alzheimer's disease brain‐derived Aβ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Luminescent‐conjugated oligo‐ and polythiophenes (LCOs and LCPs) represent a promising class of amyloid imaging agents, recognizing and differentiating a broader subset of protein aggregates than conventional amyloid dyes . It was recently shown by combinatorial ssNMR, modelling and fluorescence that the main molecular binding site for the LCO p‐FTAA appears to overlap with that described for Congo red (see more below). LCOs and LCPs contain a twistable thiophene backbone and upon conformational restriction of this backbone, different emission profiles are observed from the oligothiophene derivatives.…”
Section: Methods To Study Polymorphic Amyloidsmentioning
confidence: 99%
“…, the pyridinyl‐butadienyl‐motif in PBB3 was replaced by a bi‐thiophene vinyl moiety rendering a set of compounds denoted bi‐thiophene‐vinyl‐benzothiazoles/benzothiazoliums (bTVBTs). When utilizing the bTVBTs in combination with a thiophene‐based ligand, qFTAA‐CN selective towards aggregated Aβ species, the two pathological hallmarks in AD could easily be distinguished (Fig. d).…”
Section: Targeting Taumentioning
confidence: 99%